The sweat of their face : portraying American workers - Ward, David C., 1952-; Moss, Dorothy; Fagg, John, 1977- (Smithsonian Books ; In association with the National Portrait Gallery, 2017)
"Published to accompany an exhibition at the National Portrait Gallery, Smithsonian Institution, Washington, DC"--Colophon.